Keabsahan Pembelian Properti Dalam Perkawinan Tanpa Persetujuan Pasangan: Perspektif Hukum Indonesia - Ramaputra, Ngurah Aldi; Dwijayanthi, Putri Triari (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
The purpose of this study was to examine the validity of buying property in a marital relationship without the consent of the spouse and to analyze the legal consequences that arise if property buying and selling activities are carried out without the consent of the spouse who is still bound by a legal marriage relationship. This was normative legal research using several approaches, namely statutory approach, conceptual approach and analytical approach. The study indicated that in the event that the husband of wife uses the shared asset to buy property, then it must be carried out with the consent of both parties. In the event that the agreement is carried out with only the approval of one party, then it becomes null and void, bear in mind that the objective element as a legitimate requirement for the agreement is not fulfilled.